VD_FINDINFO HC / 2014 / 69 vom 3. Februar 2014 - VD Tribunal cantonal (2014)
DEMEURE DU DÉBITEUR, LOYER, RÉSILIATION, EXPULSION DE LOCATAIRE | 257d CO, 257 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 318 al. 1 CPC (CH)